The discourse of court interpreting : discourse practices of the law, the witness, and the interpreter - Hale, Sandra Beatriz (Benjamins translation library, 2004)
This book explores the intricacies of court interpreting through a thorough analysis of the authentic discourse of the English-speaking participants, the Spanish-speaking witnesses and the interpreters. Written by a practitioner, educator and researcher, the book presents the reader with real issues that most court interpreters face during their work and shows through the results of careful research studies that interpreter's choices can have varying degrees of influence on the triadic exchange. It aims to raise the practitioners' awareness of the significance of their choices and attempts to.